Compilation and Dissemination of Lithuanian Paremias: Contemporary Resources - Zaikauskienė, Dalia (Vilnius University Open Series, 2021)
The Collection of Lithuanian Proverbs and Proverbial Phrases built by the Institute of Lithuanian Literature and Folklore in Vilnius presents a thorough view of the corpus of traditional paremias. A larger part of the Collection consists of archival data, another one – of paremias collected from written sources.Archival data – that is paremias mostly from the Lithuanian Folklore Archive (LTR), Lithuanian Scientific Society’s Archive (LMD). These texts are mainly samples of the spoken language and dialects. The oldest archive collections are from the 19th century. Another large part of Lithuanian paremias compilation consists of texts collected from written sources. It is worth to mention, that we have around 1500 proverbs from the period of the 16th to the 18th centuries.The collection is accessible through three resources: they are the Card Index, the publication “Lithuanian Proverbs and Proverbial Phrases” (LPP), and The Electronic Compilation of Proverbs and Proverbial Phrases (eLPP).The Card Index was the first organized and systematized resource of Lithuanian paremias and served as the base for LPP and eLPP. The Card Index was created in 1970–1990 following the initiative of professor Kazys Grigas, who was also the author of the system of it. There are around 50 000 proverb types and more than 200 000 variant texts in the Card Index.At the end of the 20th century, LPP was started to be compiled. There have been three volumes published until now (Vol. 1 – 2000, Vol. 2 – 2008, Vol. 3 – 2019). LPP presents carefully sorted data without duplicates, copies, and fakes, and it has some additional data: Lithuanian paremias equivalents (in Latvian, Polish, German, English, Latin, and Russian) and type titles’ translations into English, German, and Russian.In 1998, eLPP was started and in 2018, after receiving funding from the Lithuanian Research Council (LMTLT), the database was updated. Now, the database also has an English version. eLPP includes the Card Index’ data and LPP data as well, with an exception of paremias variants. Due to the recently observed rising need to find an explanation of a saying, the category “Interpretation” has been introduced. The newly programmed search engine now contains functions of a simple search, advanced search, and selection lists. The database address is http://archyvas.llti.lt/elpp/lt, an email for comments and questions is patarles@llti.lt.
Keywords: proverb; proverbial phrase; paremia; resources of Lithuanian paremias; type; variant; equivalent